COLLABORATION OF THE ACCOUNTING EDUCATION STUDY PROGRAM OF THE UNIVERSITY OF PGRI WEST SUMATRA WITH STATE VOCATIONAL SCHOOL 1 LUBUK SIKAPING AS A GUEST LECTURER IN THE FIELD OF ACCOUNTING ACCURATE SOFTWARE - Harini, Gustia; Syamra, Yesmira; Amelia, Mona; Pratama, Indra Mulia; Benia, Gelsa Juni; Putri, Tiara Dian (Universitas PGRI Sumatera Barat, 2025)
Quality human resources are inseparable from the quality of education available. This condition will certainly encourage the education sector to continue preparing educational systems and materials to prepare students who are able to compete and meet all current challenges. The development of the 4.0 revolution requires us to be able to understand and practice existing computer applications, one of which is computer applications using Accurate Accounting software. In fact, every company must develop its system according to the complexity, company development, and to keep up with the times. Several types of computer accounting applications that have been widely used in the world are Accurate Accounting. To keep up with all these technological advances, students must be prepared to face these developments and teachers are provided with provisions to be proficient in using these programs. Providing practical computer accounting training for vocational high school teachers aims to provide teachers with vocational skills competencies to improve their abilities in training their students to become productive individuals, able to work independently or fill job openings in the workforce as middle-level workers. This activity seeks to provide a correct understanding of accounting by using Accurate applications to assist in preparing financial reports.